English Made Easy - Hosler, Mary Margaret (New Delhi McGraw-Hill, 2013)
Intended for use in quarter or semester courses in business English or basic English skills, this text-workbook covers the essentials of grammar, punctuation, style, capitalization, number usage, word usage, and paragraph development.
Include Index
Keywords: English language--Business English -- English language--Grammar